2019
DOI: 10.1080/16549716.2018.1522149
|View full text |Cite
|
Sign up to set email alerts
|

Empowering sex workers? Critical reflections on peer-led risk-reduction workshops in Soweto, South Africa

Abstract: Background: Sex workers in South Africa face various forms of structural and interpersonal violence, including police violence, exclusion from health services, and stigmatization and marginalization within their communities. In an attempt to counteract the harmful health effects of criminalization and exclusion, risk-reduction workshops are a key component of HIV prevention programs globally. This paper offers a critical investigation of Creative Space workshops – a South African model of risk-reduction worksh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Examples of GBV prevention, response, and accountability through victim identification, care, and support were supported by promising practice reports across FSW (Bhattacharjee, Musyoki, et al, 2018; Dayton et al, 2020; Janssen et al, 2009; Longwill et al, 2012), MSM (Betron, 2009; Bhattacharjee, Musyoki, et al, 2018; Dayton et al, 2020; Wertheimer, 1990), and PWID (Foreman-Mackey et al, 2019; Janssen et al, 2009). These approaches included health system–based GBV screening and referral for MSM (Betron, 2009); peer educator delivered empowerment and support services (Bhattacharjee, Morales, et al, 2018; Bhattacharjee, Musyoki, et al, 2018; Huschke, 2019), rapid crisis response, counseling and access to care and justice for FSW (Euser et al, 2012; Longwill et al, 2012), and MSM (Wertheimer, 1990); and street-based safe spaces for PWID and PWID-FSW, which generated reductions in violence and an improved sense of safety (Foreman-Mackey et al, 2019; Janssen et al, 2009). The Anti-Violence Project of New York City (Wertheimer, 1990) embedded rights promotion within the crisis response system.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of GBV prevention, response, and accountability through victim identification, care, and support were supported by promising practice reports across FSW (Bhattacharjee, Musyoki, et al, 2018; Dayton et al, 2020; Janssen et al, 2009; Longwill et al, 2012), MSM (Betron, 2009; Bhattacharjee, Musyoki, et al, 2018; Dayton et al, 2020; Wertheimer, 1990), and PWID (Foreman-Mackey et al, 2019; Janssen et al, 2009). These approaches included health system–based GBV screening and referral for MSM (Betron, 2009); peer educator delivered empowerment and support services (Bhattacharjee, Morales, et al, 2018; Bhattacharjee, Musyoki, et al, 2018; Huschke, 2019), rapid crisis response, counseling and access to care and justice for FSW (Euser et al, 2012; Longwill et al, 2012), and MSM (Wertheimer, 1990); and street-based safe spaces for PWID and PWID-FSW, which generated reductions in violence and an improved sense of safety (Foreman-Mackey et al, 2019; Janssen et al, 2009). The Anti-Violence Project of New York City (Wertheimer, 1990) embedded rights promotion within the crisis response system.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, across different countries, the fight for sex workers' rights has often been framed in the context of improving public health (Healy et al, 2010;Jenness, 1990). Previous studies on sex worker community initiatives that aim to empower sex workers have found that these initiatives are often sponsored by public health organisations that aim to reduce cases of HIV/AIDS and other sexually transmitted infections through education and safer sex practices (Huschke, 2019;Jeffreys, 2018). Huschke (2019) has observed that many sex worker peer-education programmes are funded by and based on 'biomedical models of disease control with the aim of changing the behaviour of individuals to reduce HIV and other STIs' (p. 7).…”
Section: Funding For Sex Worker Rightsmentioning
confidence: 99%
“…Previous studies on sex worker community initiatives that aim to empower sex workers have found that these initiatives are often sponsored by public health organisations that aim to reduce cases of HIV/AIDS and other sexually transmitted infections through education and safer sex practices (Huschke, 2019;Jeffreys, 2018). Huschke (2019) has observed that many sex worker peer-education programmes are funded by and based on 'biomedical models of disease control with the aim of changing the behaviour of individuals to reduce HIV and other STIs' (p. 7). Since the rise of the HIV epidemic in the 1980s and 1990s, sex work has become a major focus in epidemiological studies, with research on HIV/STIs dominating in the sex work research literature (Murray et al, 2018).…”
Section: Funding For Sex Worker Rightsmentioning
confidence: 99%
“…32 Given the social barriers to health care that sex workers face, multiple international programs recruit sex workers as educators and support them in teaching their peers about various health topics, especially risk reduction and mental health. 17,[33][34][35][36] Such programs benefit learner and educator alike, fostering community mobilization, reduced internalized stigma, and empowerment. 17,[33][34] One of the first programs to combine peer education with service learning in medical education was pioneered by Dr. Rachel Robitz and colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…17,[33][34][35][36] Such programs benefit learner and educator alike, fostering community mobilization, reduced internalized stigma, and empowerment. 17,[33][34] One of the first programs to combine peer education with service learning in medical education was pioneered by Dr. Rachel Robitz and colleagues. Founded in 2011, Women Leading Healthy Change (WLHC) is a partnership between the University of Cincinnati College of Medicine and a local community organization that provides transitional housing, education, and support to sex workers.…”
Section: Introductionmentioning
confidence: 99%